Communication identity of digital immigrant micro-entrepreneur in adapting to promotional innovation - Widiyanti, Amelia; Pamungkas, Indra Novianto Adibayu (Manajemen Komunikasi, 2025)
The digital era requires an entrepreneur to adapt through innovation, especially in terms of promotion to the audience with an identity that adjusts to changes. Promotion adaptation plays an essential role in increasing business capacity and competitiveness. This research aims to identify the communication identities of micro business actors, including digital immigrant groups, and their adaptation to promotional innovations. This research uses a qualitative method by interviewing thirty informants of micro business actors in West Java who were born before 1981. This research uses data processing techniques through a coding process using NVivo software. The study results show that the identity formed through social interaction of micro business actors is closely related to the decision to adopt promotions. Micro-business actors have a friendly and sociable nature that makes it easiand er for them to access information. In addition, they are also curious and confident, so they encourage them to learn many new things that can advance their business. Micro-business actors of the immigrant digital group acquire these traits from the influence of “someah” culture and a supportive environment. The communication identity or self-concept owned by micro business actors in West Java provides opportunities for them to develop themselves in terms of receiving innovation, especially in terms of promotion. In addition, the acceptance of innovation is closely related to the character and self-concept of micro-business actors. The importance of support from the government, the surrounding environment, and stakeholders to make it easier for micro business actors to accept an innovation.